A style discussion of Strange Quartet, Wits Trio Tribute, and Quin-tête-à-tête : three chamber works of Jeanne Zaidel-Rudolph composed between 2000-2019 - Johnson, Alexander F. (University of Pretoria, 2022)
Thesis (DMus (Composition))--University of Pretoria, 2021.